Pengaruh Status Sosial, Perhatian Orang Tua, Motivasi Belajar, dan Fasilitas Belajar terhadap Hasil Belajar Siswa SMP Islam Al Chusnaini Sidoarjo - Maulidia Ilham Fadilah; Laila Badriyah; Sholehuddin Sulaiman (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2025)
Purpose: This study aims to determine and analyze the factors influencing student learning outcomes at SMP Islam Al Chusnaini, Sidoarjo, focusing on the variables of social status, parental attention, learning motivation, and learning facilities. Design/methodology/approach: This research employs a quantitative approach with a survey method. The population comprises all 84 students of SMP Islam Al Chusnaini, Sidoarjo, using a total sampling technique. Data collection methods include observation, interviews, and questionnaires. The collected data were analyzed using multiple linear regression analysis. Findings: The results indicate that: (1) Social status has a significant positive effect on student learning outcomes; (2) Parental attention shows a significant negative effect on student learning outcomes; (3) Learning motivation has a significant positive effect on student learning outcomes; (4) Learning facilities have a significant positive effect on student learning outcomes. Research limitations/implications: This study is limited to one educational institution (SMP Islam Al Chusnaini, Sidoarjo) within a specific timeframe. The findings regarding parental attention suggest a need for further qualitative exploration into the dynamics of parental involvement at the research site. Originality/value: This research contributes by examining a unique combination of four key factors (social status, parental attention, motivation, and facilities) within the context of an Islamic middle school. The unexpected finding of a negative relationship between parental attention and learning outcomes offers a novel perspective for further investigation in similar educational settings